2016
DOI: 10.1038/npp.2016.84
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Metabolites, Volume and Cortical Thickness in Antipsychotic-Naive Patients with First-Episode Psychosis: Implications for Excitotoxicity

Abstract: Neuroimaging studies investigating patients with schizophrenia often report appreciable volumetric reductions and cortical thinning, yet the cause of these deficits is unknown. The association between subcortical and cortical structural alterations, and glutamatergic neurometabolites is of particular interest due to glutamate's capacity for neurotoxicity; elevated levels may be related to neuroanatomical compromise through an excitotoxic process. To this end, we explored the relationships between glutamatergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 52 publications
5
38
0
Order By: Relevance
“…The current model of inefficient self-stabilization predicts that in early stages, higher levels of glutamate signal can be found in the loci of hyperconnectivity and anomalously increased neural activity whereas lower levels of glutamate signal should accompany grey matter loss in schizophrenia, especially in later stages of illness, with excitatory synapses undergoing structural elimination. While several studies are in agreement 69,75,229,234,235 , opposite results also exist 236 . Cautious interpretation is required nevertheless as it is unclear how much of spectroscopic glutamate refers to synaptic activity.…”
Section: Gaba and Glutamate Systemsupporting
confidence: 50%
“…The current model of inefficient self-stabilization predicts that in early stages, higher levels of glutamate signal can be found in the loci of hyperconnectivity and anomalously increased neural activity whereas lower levels of glutamate signal should accompany grey matter loss in schizophrenia, especially in later stages of illness, with excitatory synapses undergoing structural elimination. While several studies are in agreement 69,75,229,234,235 , opposite results also exist 236 . Cautious interpretation is required nevertheless as it is unclear how much of spectroscopic glutamate refers to synaptic activity.…”
Section: Gaba and Glutamate Systemsupporting
confidence: 50%
“…For example, increased striatal glutamate levels measured with proton magnetic resonance spectroscopy ( 1 H‐MRS) have also been observed in patients with first‐episode psychosis [Plitman et al, ]. In turn, striatal glutamate levels were found to be negatively correlated with dorsal caudate volumes in these patients [Plitman et al, ]. Given the potential interactions between striatal DA and glutamate [Caravaggio et al, ; Stone et al, ], it can be inferred that the dopaminergic changes observed in schizophrenia may also be related changes in brain morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for total brain volume (TBV) analysis has been published elsewhere [Plitman et al, ]. TBV was obtained using the Brain Extraction based on non‐local Segmentation Technique (BEaST) method [Eskildsen et al, ], which is based on non‐local segmentation in a multi‐resolution framework.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for total brain volume (TBV) analysis has been published elsewhere . Total brain volume was obtained using the brain extraction based on a nonlocal segmentation technique method .…”
Section: Methodsmentioning
confidence: 99%